The Relationship Between Religiosity and Student Learning Achievement in Chemistry - Nasution, Nurul Amaliah; Darmana, Ayi (UNDIKMA, 2024)
This research aim to find out relationship between religiosity and students`' chemistry learning achievement, is correlational research that aims to understand the relationship between the independent variable and the dependent variable. This research is quantitative descriptive research, so in collecting data the researcher used a questionnaire method, describing and explaining which dimensions of religiosity are more related to the chemistry learning achievement of class XI MIPA students. In this research, there are two variables, namely one independent variable in the form of students'' level of religiosity, and one dependent variable in the form of students'' chemistry learning achievement. For further research, correlational research on these two variables must be expanded by adding additional criteria. For example, criteria can be added to the dimension of religiosity. In addition, tools must be created to assess students'' chemistry learning achievements.